Causality between Defence Spending and Economic Growth in Sub-Saharan Africa: Evidence on a Controversial Empirical Issue - Masih, Zahra Naoar (International Journal of Economics and Financial Issues, 2017)
Identifying the proper links toward stimulating economic growth has been a debate among economists for years. To analyse potential variables, this paper utilizes the Granger Causality Test between economic growth and defense spending. Unlike previous studies, this paper illustrates the relationship by finding cointegration between the variables (i.e. long-term equilibrium relationship). We test for cointegration between defense spending and real income in a sample of Sub-Saharan African nations. By using a dynamic vector error-correction model, we analyse the direction of Granger-causation and hence the within-sample Granger-exogeneity or endogeneity of each of the variables. The relative strength of the causality is gauged (through the dynamic variance decomposition technique) by decomposing the total impact of an unanticipated shock to each of the variables beyond the sample period, into proportions attributable to shocks in the other variables including its own, in the bivariate system. Results based on these tools of methodology, broadly tend to indicate that, defence spending and economic growth did share a common trend over the sample period under analysis, but it was the former which stimulated the latter. Our study found Kenya and Niger as subject to defense spending, and Sudan, Mali and Tanzania experiencing predicted bidirectionality. It is defence spending that has a much more pronounced and permanent effect on economic growth, giving rise to implications: although expenditure on defence may have been politically motivated, over the long-run this spending did play a significant role in enhancing impact on a closed-door economy. Keywords: defence-growth causality, cointegration, vector error-correction model, Granger error-correction causation. JEL Classifications: O11, C22, C32, C52